Non-pharmacological interventions of traditional Chinese medicine in treating polycystic ovary syndrome: a group consensus - Tianyi Zhou; Fangfang Wang; Xinfen Xu; Yuhang Zhu; Rong Zhang; Hye Won Lee; Xiao-Yang Mio Hu; Fan Qu; Minchen Dai; Yijing He; Xinyue Li; Zhichun Jin; et al. (Integrative Medicine Research)
Background: To make a group consensus about non-pharmacological interventions of traditional Chinese medicine in treating polycystic ovary syndrome based on the previous guidelines, literature, and expert viewpoints. Methods: Organized by Chinese Integrative Medicine & Traditional Chinese Medicine Academy, Chinese Maternal and Child Health Association, China, 29 experts from 18 Chinese provinces and 2 international experts, who specialize in gynecology, obstetrics, pediatrics, endocrinology, cardiovascular, psychology, reproductive genetics, nursing, acupuncture and tuina, traditional Chinese medicine, integrative medicine, and other disciplines, discussed and revised the recommendations one by one through in-person or online communication. Each recommendation was approved by ≥90% of the experts before it could be established. The main outcome measure is an optimal clinical regimen for addressing the requirements of women with PCOS and improving their quality of life. Result(s): The writing panel drafted the initial report, following a consensus process via adequate communication, which was then reviewed and revised by the consensus panel. This consensus provides 12 non-pharmacological interventions (including acupuncture, thumbtack needle, thread-embedding therapy, TEAS, AA, acupoint hot compress, cupping, acupressure, moxibustion, five elements music, aromatherapy, traditional Chinese exercises) for 8 phenotypes of PCOS, resulting in 34 items of clinical practice recommendations. Conclusion(s): The consensus provides 12 non-pharmacological interventions of traditional Chinese medicine for 8 phenotypes of PCOS, resulting in 34 items of clinical practice recommendations, which may be improved by more high-quality multicenter clinical trials.